Factors Affecting Utilization of Antenatal Care Services Among Women Visiting for Institutional Delivery in Tertiary Hospital, Bhairahawa, Nepal: A Cross Sectional Study - Shrestha, Rubina; Bhusal, Chet Kant; Chhetri, Pradip; Shrestha, Saneep; Priyanka, Jyoti (Journal of Universal College of Medical Sciences, 2021)
INTRODUCTION: Antenatal Care (ANC) services utilization during pregnancy plays an important role in prevention and management of pregnancy related complication thus improving the maternal and child health. Hence this study aimed to identify the factors influencing utilization of ANC service among women visiting for institutional delivery in tertiary hospital of Bhairahawa, Nepal. MATERIAL AND METHODS: Hospital based cross-sectional study was carried among 396 women admitted in the postnatal ward of Universal College of Medical Sciences and Teaching Hospital, Bhairahawa, Nepal form September 2019 to December 2019 following ethical clearance and verbal consent from participants. Variables with significant association (p<0.05) in bivariate analysis were entered into multivariate logistic regressions to find the factors affecting utilization of antenatal care services. RESULTS: This study revealed that 18.43% of respondents did not receive any ANC services. Among those who were not receiving ANC service, 86.3% never felt the need for ANC services throughout the period of pregnancy. ANC service utilization was found to be associated with religion (AOR=3.15, 95% CI: 1.40-7.08) and husband education (AOR=5.09, 95% CI: 1.63-15.92). CONCLUSION: In spite of being an essential component for the care of pregnant women ANC services was not utilized by all of them as many of them did not felt the need of this service. Thus it is recommended to increase awareness regarding the available services and its importance by local stakeholders to prevent further morbidity and mortality.